Effects of unemployment and inflation on the economy of Nepal - Kumar, Nand Kishor (Rajarshi Janak University Research Journal, 2024)
This is a longitudinal study for the period of 2010-2019 which examines the effect of inflation and unemployment on growth rate of Nepal. The economy of Nepal suffers from inflation and unemployment. In this paper, the impact of inflation and unemployment on growth rate in the two short-run and long-run phases was investigated and examined using Karl Pearson`s Co-efficient and Phillips Curve. The results of this model showed the significance and positive effect of inflation and unemployment on economic growth in short-run and negative effect on long-run. This paper found that policy maker should conscientiously focus on strategies to reduce and control inflation and unemployment. The planner could attempt to reduce and control over unemployment and inflation to get desired economic growth of Nepalese economy. From 2010 to 2019, Nepal's economy faced significant challenges and transformations. Understanding the interplay between inflation and unemployment during this period highlights the complexity of macroeconomic management in a developing country. Policy responses need to be multifaceted, considering both immediate economic pressures and long-term structural changes.